IMPLEMENTASI SUPERVISI AKADEMIK KEPALA MADRASAH TSANAWIYAH DI PONDOK PESANTREN MANBA'U DARISSALAM PALANGKA RAYA - Lailatul Asvia; Fahmi Fahmi; Slamet Riyadi (STKIP Pesisir Selatan, 2026)
This study aims to analyze and describe the implementation of academic supervision by the principal at Madrasah Tsanawiyah Pondok Pesantren Manba'u Darissalam Palangka Raya, focusing on the supervision of the preparation of lesson plans (RPP), the implementation of learning in the classroom, and the assessment of learning. This study uses a qualitative approach with a case study type to obtain an in-depth picture of supervisory practices in madrasahs. Data were collected through interviews with the madrasah principal and subject teachers, observation of the learning process in the classroom, and documentation studies of learning tools. Data validity was ensured through source and technique triangulation, and data analysis was carried out through the stages of data condensation, data presentation, and systematic conclusion drawing. The results of the study indicate that the principal's academic supervision has not been implemented optimally because it is not yet planned, systematic, or sustainable, and is not supported by a standard supervision schedule and instruments. The supervision carried out is still administrative in nature, does not touch on the aspects of in-depth professional development of teachers, and does not provide constructive feedback for improving the quality of learning and student learning outcomes. This condition indicates the need for comprehensive and continuous improvement in the planning, implementation, and evaluation of supervision.